Studies on nucleophilic enzymes involved in the cell wall biosynthesis of Mycobacterium tuberculosis - de Munnik, M (2024)
The extraordinarily thick and complex cell wall of Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), may be considered as an Achilles’ heel of the bacillus; however, the most important class of antibiotics targeting the bacterial cell wall (the β-lactams) has not been proven to be effective as TB treatment, likely in part due to resistance mechanisms, such as hydrolysis catalysed by the β-lactamase BlaC. β-Lactams are inhibitors of a class of transpeptidases of the peptidoglycan layer of the bacterial cell wall, i.e., the penicillin binding proteins (PBPs). Mtb additionally applies a second class transpeptidases, the L,D-transpeptidases (Ldts), which employ a nucleophilic cysteine in catalysis, and which are reported to be resistant to inactivation by most β-lactams.